Clinical spectrum of impulse control disorders in Parkinson's disease. Issue 2 (5th November 2014) - Weintraub, Daniel; David, Anthony S.; Evans, Andrew H.; Grant, Jon E.; Stacy, Mark; Stacy (Chair), Mark; Lang, Anthony; Napier, Celeste; Samuel, Michael; Strafella, Antonio; Weintraub, Daniel
Abstract Impulse control disorders (ICDs), including compulsive gambling, buying, sexual behavior, and eating, are a serious and increasingly recognized psychiatric complication in Parkinson's disease (PD). Other impulsive‐compulsive behaviors (ICBs) have been described in PD, including punding (stereotyped, repetitive, purposeless behaviors) and dopamine dysregulation syndrome (DDS; compulsive PD medication overuse). ICDs have been most closely related to the use of dopamine agonists (DAs), perhaps more so at higher doses; in contrast, DDS is primarily associated with shorter‐acting, higher‐potency dopaminergic medications, such as apomorphine and levodopa. Possible risk factors for ICDs include male sex, younger age and younger age at PD onset, a pre‐PD history of ICDs, and a personal or family history of substance abuse, bipolar disorder, or gambling problems. Given the paucity of treatment options and potentially serious consequences, it is critical for PD patients to be monitored closely for development of ICDs as part of routine clinical care. © 2014 International Parkinson and Movement Disorder Society